FACTORS AFFECT STOCK PRICES ON MANUFACTURING COMPANIES LISTED ON IDX BEFORE AND DURING COVID-19 PANDEMIC - Tirtadjaya, Tia Talia; Yanti, Yanti (Graduate Program of Universitas Tarumanagara, 2023)
This research aims to empirically examines the effect of Earning Per Share, Return On Assets, Debt to Equity Ratio, Quick Ratio, Dividend Payout Ratio, and Dividend Yield on the stock prices of manufacturing companies listed on IDX before and during COVID-19 pandemic, also empirically examines the differences on stock prices of manufacturing companies listed on IDX before and during COVID-19 pandemic. This research using 52 samples of manufacturing companies that listed on IDX for the 2019-2020 period. The 2019 data represent conditions before COVID-19 pandemic and the 2020 data represent conditions during COVID-19 pandemic. The results of this research are Earning Per Share and Dividend Payout Ratio effects significantly positive towards stock prices either before or during COVID-19 pandemic.